The role of augmentative and alternative communication for children with autism: current status and future trends - Iacono T (Dove Medical Press, 2016)
Teresa Iacono,1 David Trembath,2 Shane Erickson3 1Living with Disability Research Centre, La Trobe University, Bendigo, VIC, Australia; 2Menzies Health Institute Queensland, Griffith University, Gold Coast, QLD, Australia; 3Living with Disability Research Centre, La Trobe University, Melbourne, VIC, Australia Background: Augmentative and alternative communication (AAC) interventions are used for children with autism, often as stand-alone communication interventions for those who are minimally verbal. Our aim was to synthesize the evidence for AAC interventions for children (up to 21 years), and then consider the role of AAC within established, comprehensive, evidence-based autism interventions targeting learning across multiple developmental domains.Design: We completed a systematic search of three databases (OVID Medline, PsycINFO, ERIC) as well as forward citation and hand searches to identify systematic reviews of AAC intervention efficacy research including children with autism, published between 2000 and March 2016 in peer-reviewed journals. Data pertaining to the quality indicators of included studies, effect sizes for intervention outcomes, and evidence for effectiveness were extracted for descriptive analysis.Results: The search yielded 17 systematic reviews. Most provided indicators of research quality for included studies, of which only relatively few provided conclusive results. Communication targets tended to be focused on teaching children to make requests. Still, effect size measures for included studies indicated that AAC was effective to highly effective.Conclusion: There is growing evidence for the potential benefits of AAC for children with autism, but there is a need for more well-designed studies and broader, targeted outcomes. Furthermore, a lack of evidence for the role of AAC within comprehensive intervention programs may account for a tendency by autism researchers and practitioners to neglect this intervention. Attempts to compare evidence for AAC with other interventions for children with autism, including those in which the use of AAC is delayed or excluded in pursuit of speech-only communication, must take into account the needs of children with the most significant learning needs. These children pose the greatest challenges to achieving large and consistent intervention effects, yet stand to gain the most from AAC interventions. Keywords: autism, augmentative and alternative communication, intervention, research synthesis